A Comparative Study on the Effectiveness of Rood’s Approach Versus Combined Rood’s Approach and Facial Proprioceptive Neuromuscular Facilitation (PNF) in Patients with Bell’s Palsy - Yadav, Savitri; Lohar, Deepak; Khan, Jafar; Warsi, Rahat khan; Menria, Shubham; Rai, Richa Hirendra; pal, Renuka (Journal of Neonatal Surgery, 2025)
Background:Bell’s palsy is an acute idiopathic facial nerve paralysis that affects the seventh cranial nerve, causing sudden unilateral facial muscle weakness. While Rood’s Approach and Facial Proprioceptive Neuromuscular Facilitation (PNF) are both recognized in physiotherapeutic management, there is limited evidence comparing their individual and combined effectiveness in facial palsy rehabilitation. Objective:To compare the effects of Rood’s Approach alone versus its combination with Facial PNF in improving facial muscle function in Bell’s palsy patients using the House-Brackmann (HB) grading system. Methodology: A comparative interventional study was conducted on 30 patients diagnosed with Bell’s palsy. Participants were randomly divided into two groups: Group A received Rood’s Approach alone, while Group B received Rood’s Approach combined with Facial PNF. Interventions were provided over an 8-week period, and outcomes were assessed pre- and post-treatment using the HB grading system. Data were analyzed using paired and independent t-tests with significance set at p < 0.05. Results: Both groups showed significant improvements post-treatment. Group A improved by a mean of 2.67 HB grade points, while Group B showed greater improvement with a mean change of 3.40. Although the between-group difference was not statistically significant, the clinical outcomes favored the combined approach, suggesting enhanced neuromuscular recovery. Conclusion: Both interventions were effective in improving facial function in Bell’s palsy patients. However, the combination of Rood’s Approach with Facial PNF provided superior clinical benefits, supporting its recommendation as a more effective rehabilitation protocol.